Meeting future NOX emission regulations by adding an electrically heated mixer - Meruva, P.; Matheaus, A.; Sharp, C. A.; McCarthy, J. E.; Masoudi, M.; Poliakov, N.; Noorfeshan, S. (Frontiers in Mechanical Engineering, 2022)
New regulations by the California Air Resources Board (CARB) demand stringent 0.02 g/hp-hr tailpipe NOx limit by the year 2027, requiring Selective Catalytic Reduction (SCR) catalysts to provide high NOx conversions even at low (below 200° C) exhaust temperatures. This work describes utilizing an Electrically Heated Mixer System (EHM system) upstream of a Light-Off Selective Catalytic Reduction (LO-SCR) catalyst followed by a conventional aftertreatment system containing DOC, DPF and SCR, enabling high NOx conversions meeting CARB’s NOx emission target. The aftertreatment catalysts were hydrothermally aged to Full Useful Life. Conventional unheated Diesel Exhaust Fluid (DEF) was injected upstream of both the LO-SCR and primary downstream SCR. The EHM system allowed for DEF to be injected in as low as 130° C upstream of the LO-SCR, while in previous studies, unheated DEF was injected at 180° C or dosed at 130° C with heated DEF. The combination of unheated DEF, EHM system, LO-SCR and downstream SCR enabled the needed increase in NOx efficiency in low exhaust temperatures which was observed in drive cycles such as in cold-FTP, LLC and WHTC. There were several-fold reductions in tailpipe NOx using this configuration when compared to its baseline: 3.3-fold reduction in FTP, 22-fold in Low Load Cycle, 38-fold in Beverage Cycle, 8-fold in “Stay Hot” cycle and WHTC by 10-fold. Finally, it is shown that EHM system can heat the exhaust gas, such as during cold start, without needing an additional heating hardware integrated into the system. These results were observed without performing changes in the engine base calibration.